2012
DOI: 10.3858/emm.2012.44.8.053
|View full text |Cite
|
Sign up to set email alerts
|

B cell-associated immune profiles in patients with end-stage renal disease (ESRD)

Abstract: Most of the previous studies on immune dysregulation in end-stage renal disease (ESRD) have focused on T cell immunity. We investigated B cell subpopulations in ESRD patients and the effect of hemodialysis (HD) on B cell-associated immune profiles in these patients. Forty-four ESRD [maintenance HD patients (n = 27) and pre-dialysis patients (n = 17)] and 27 healthy volunteers were included in this study. We determined the percentage of B cell subtypes, such as mature and immature B cells, memory B cells, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
2
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 35 publications
3
48
2
3
Order By: Relevance
“…25 A recent study also indicated a significant decrease in memory B cells in hemodialysis group; however, these cells were significantly higher in the pre-dialysis group compared to the hemodialysis group while immature B cells were significantly lower in the pre-dialysis group. 17 It suggested that there was defective regulatory activity in Figure 1. Association of NK cell proportion, B cell proportion, and eGFR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 A recent study also indicated a significant decrease in memory B cells in hemodialysis group; however, these cells were significantly higher in the pre-dialysis group compared to the hemodialysis group while immature B cells were significantly lower in the pre-dialysis group. 17 It suggested that there was defective regulatory activity in Figure 1. Association of NK cell proportion, B cell proportion, and eGFR.…”
Section: Discussionmentioning
confidence: 99%
“…12 Several studies indicated a reduction of peripheral blood T and B lymphocytes in patients with ESRD; however, the result remains controversial. [13][14][15][16][17][18][19] Of note, most of these studies on immune dysfunction have been restricted to ESRD patients. This is necessarily inadequate for the full understanding of impacts of CKD on immune system.…”
Section: Introductionmentioning
confidence: 99%
“…4 ). The studies included in this additional analysis are Lisowska et al [13] , Kim et al [22] and Zhang et al [23] . This analysis aimed to understand if the difference measured between CKD G5D patients and HCs is due to uremic state or hemodialysis treatments.…”
Section: Treg Cells In Ckd G5 Versus Hc and Ckd G5d Versus Ckd G5mentioning
confidence: 99%
“…Five studies that included comparable HC and CKD G5D patients and used similar criteria for determining the percentage of Treg cells in total CD4 T-cells were subjected to a meta-analysis [13,[21][22][23][24] . The complete list of articles included in the systematic review is described in table 1 .…”
Section: Study Characteristics and Selectionmentioning
confidence: 99%
“…18 Significantly altered B cell-associated immunity is a wellknown phenomenon related to GFR category 5 (end-stage renal disease, ESRD). 19 Pahl et al clearly showed that B-cell lymphopenia is associated with the downregulation of B-cell activating factor (BAFF) receptor in transitional B cells. This resulted in resistance to the biological actions of BAFF being a potent B-cell differentiation and survival factor.…”
Section: Ckd As An Immunocompromised Statementioning
confidence: 99%